Radiosynthesis of [11C]Ibrutinib via Pd-Mediated [11C]CO Carbonylation: Preliminary PET Imaging in Experimental Autoimmune Encephalomyelitis Mice - Lindberg, Anton; Boyle, Amanda J.; Tong, Junchao; Harkness, Michael B.; Garcia, Armando; Tran, Tritin; Zhai, Dongxu; Liu, Fang; Donnelly, David J.; Vasdev, Neil (Frontiers in Nuclear Medicine, 2021)
Ibrutinib is a first generation Bruton’s tyrosine kinase (BTK) inihibitor that has shown efficacy in autoimmune diseases and has consequently been developed as a positron emission tomography (PET) radiotracer. Herein, we report the automated radiosynthesis of [11C]ibrutinib through 11C-carbonylation of the acrylamide functional group, by reaction of the secondary amine precursor with [11C]CO, iodoethylene, and Palladium-NiXantphos. [11C]Ibrutinib was reliably formulated in radiochemical yields of 5.4 ± 2.5 % (non-decay corrected; n = 9, relative to starting [11C]CO2), radiochemical purity >99%, and molar activity of 58.8 ± 30.8 GBq/µmol (1.55 ± 0.83 Ci/µmol). Preliminary PET/magnetic resonance imaging with [11C]ibrutinib in experimental autoimmune encephalomyelitis (EAE) mice showed a 49% higher radioactivity accumulation in the spinal cord of mice with EAE scores of 2.5 vs. sham mice.